2013
DOI: 10.1128/jvi.02747-12
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating Macrophages Are Key to the Development of Seizures following Virus Infection

Abstract: b Viral infections of the central nervous system (CNS) can trigger an antiviral immune response, which initiates an inflammatory cascade to control viral replication and dissemination. The extent of the proinflammatory response in the CNS and the timing of the release of proinflammatory cytokines can lead to neuronal excitability. Tumor necrosis factor alpha (TNF-␣) and interleukin-6 (IL-6), two proinflammatory cytokines, have been linked to the development of acute seizures in Theiler's murine encephalomyelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
174
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(184 citation statements)
references
References 53 publications
8
174
2
Order By: Relevance
“…In murine models of CNS disease, either degenerative or as a result of viral infection, the infiltration of activated monocytes defined as blood-derived MNCs expressing Ly6C hi and CCR2 (iMo) has been associated with sustained inflammation and increased pathology (67,(69)(70)(71)(72)(73)(74). We next analyzed the activation state of iMo infiltrating the CNS of MCMV-infected newborn mice before and after TNF-NAb treatment by measuring the expression of the CCR2 receptor, the major histocompatibility complex class II (MHC-II), and the costimulatory molecule CD80.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine models of CNS disease, either degenerative or as a result of viral infection, the infiltration of activated monocytes defined as blood-derived MNCs expressing Ly6C hi and CCR2 (iMo) has been associated with sustained inflammation and increased pathology (67,(69)(70)(71)(72)(73)(74). We next analyzed the activation state of iMo infiltrating the CNS of MCMV-infected newborn mice before and after TNF-NAb treatment by measuring the expression of the CCR2 receptor, the major histocompatibility complex class II (MHC-II), and the costimulatory molecule CD80.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is important to note that although treatment with TNF-NAb dramatically reduced the frequency of activated microglia in the brains of infected animals to levels measured in mock-infected animals, iMo that infiltrated the brains of TNF-NAb-treated animals continued to express activation markers, providing evidence that resident cells of the infected brain are not the sole determinants of inflammation in the brain in infected animals. Studies in other small-animal models of virus-induced CNS disease associated with inflammation have described the importance of infiltrating monocytes in the induction of disease (38,74,92). Furthermore, limiting the infiltration of peripheral blood monocytes, including the Ly6C hi CCR2 ϩ subset, into the CNS resulted in improved disease outcomes in murine models of amyotrophic lateral sclerosis (ALS), demyelinating diseases associated with virus infection, experimental autoimmune encephalitis (EAE), and CNS ischemia (67,69,93,94).…”
Section: Discussionmentioning
confidence: 99%
“…19 After the viruses cross the blood-brain barrier, they can cause brain damage via inflammation, and direct infection. [20][21][22] The viruses trigger an anti-viral immune response, which initiates an inflammatory cascade to control viral replication and dissemination. [20][21][22] The extent of the pro-inflammatory response in the CNS and the timing of the release of pro-inflammatory cytokines, such as tumor necrosis factor-α and interleukin-6, can lead to neuronal excitability and injury.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] The viruses trigger an anti-viral immune response, which initiates an inflammatory cascade to control viral replication and dissemination. [20][21][22] The extent of the pro-inflammatory response in the CNS and the timing of the release of pro-inflammatory cytokines, such as tumor necrosis factor-α and interleukin-6, can lead to neuronal excitability and injury. [20][21][22] We performed tests that included PCR to identify the viral pathogens, and we found no significant differences in the viral pathogens of the meningitis and encephalitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased cognitive performance correlated with increased monocyte infiltration in HIVassociated neurocognitive disorders (HAND) (1). Additionally, infiltration of monocytes was found to be important for seizure development in a mouse model of Theiler's murine encephalitis (7). Recent studies in a mouse model of experimental autoimmune encephalitis (EAE) demonstrated that CCR2 ϩ infiltrating monocytes, but not CX3CR1 ϩ microglia, were responsible for axonal demyelination (8).…”
mentioning
confidence: 99%